IMPLEMENTASI ECO-SOSIOENTERPRENEURSIP PADA PEMBUATAN SUPER GELATO DI AZALEA FARM BOYOLALI DENGAN PENDEKATAN R&D - Fanny Hendro Aryo Putro; Aris Budi Prasetyo; Yusuf Eko Rohmadi; Donna Setiawati; Sigit Muryanto; Muhammad Abdul Aziz; Dhefi Intan Lukmana; Jihan Lestari; Istiqomah Dwi Lestari; Alfilla Nurjayanti (Universitas Mataram, 2025)
Dairy goats are another dairy livestock source, alongside cows and buffalo. Goat milk has its own unique qualities compared to cow's milk. The abundance of goat milk that has not been fully utilized is a current problem for partners. The purpose of this activity is to assist and empower the Azalea Farmers Group (KWT Azalea), as a target partner, in utilizing the abundant goat milk and creating added value for the product, including super gelato ice cream. During the program, participants listened enthusiastically, and there was interaction between the speakers and participants. Participants asked many questions related to the material presented by the speakers. Participants were very pleased with this community service activity and followed it through to the end. The implementation team also gave their best throughout the program. The community service activity on the implementation of eco-socio-entrepreneurship in super gelato production at Azalea Farm Boyolali using an R&D approach was carried out well and smoothly. Partners received benefits from this activity, including processing milk into super gelato ice cream, strengthening business management, and strengthening the website. A recommendation is to reactivate the website to better promote Azalea Farm's processed products.